Kearifan Lokal Pemeliharaan Kerbau Albino di Keraton Surakarta dalam Prespektif Sosial Ekonomi - Husodo, Ayung Adhi; Mauludin, Mochamad Ali; Nurlina, Lilis (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Local knowledge is an integral part of cultural heritage that develops through the collective experiences of communities in interacting with their natural, social, and cultural environments. One form of this local knowledge is the maintenance of albino buffalo (Kerbau Bule), which are cared for by the abdi dalem (royal servants) of the Surakarta Palace. The local knowledge possessed by the abdi dalem in maintaining these buffalo reflects a spiritual, ecological, social, and human relationship within the context of Javanese culture. This study aims to examine the local knowledge system of abdi dalem in the care of albino buffalo, viewed through the lens of the five principles of livestock management (panca usaha ternak). The research method used is a case study with a qualitative approach, involving informants from both the abdi dalem and the local community around the buffalo enclosure. The results of this study show that the practice of buffalo maintenance is based on conventional livestock techniques, guided by cultural values passed down through generations. This knowledge encompasses five key aspects: breeding and reproduction, feeding, general animal husbandry practices, housing, and animal health. The maintenance of the Kerbau Bule in the enclosure located at Alun-alun Kidul also serves as a tourist attraction and provides positive economic impacts for the surrounding local community.